The Smart Door Lock Using Face Recognition Access Based on Internet Of Things (IoT) - Farrel Laogi Murjitama; Hafidz Nur Raihan; Rangga Prasetya Adiwijaya; Desi Fitriani Ramadan; Bagas Imanuel Pasaribu; Bintang A. Silalahi; Nada Nadiefah Tasman; Syafira Audri Dwijayanti; Ummu Putri Salsabila Panjaitan; Yudhi S. Purwanto (Center for Research and Community Service, Institut Informatika Indonesia (IKADO) Surabaya, 2024)
Security is one of the basic things that humans need. In relation to a house or room, the focus of security is on the door lock. Various types of door locks have been created, ranging from conventional ones with physical keys, to modern types. This modern type of door lock is also made with various ways to open it. Some use a series of codes (keypad), some use card sensors, fingerprint sensors, to the use of face recognition technology. Several door lock technologies with face recognition have also been created, but they are still expensive. The other problem is that those devices are not equipped with some fail-safe mechanisms, in case there are troubles with the device. This smart door lock is made using face recognition technology based on the Internet of Things. This lock is equipped with an ESP32cam camera integrated in the ESP8266MOD module that can recognize faces that have been registered in the database on the website. In addition, the door is also equipped with a push button to open the door from the inside, and a button as a backup if there is a malfunction of the face recognition feature. The device test indicates no apparent issues and operates smoothly. The accuracy test for the camera yields positive outcomes, reaching up to 100% in normal lighting conditions, and dropping to around 60-80% in blur condition. Accuracy is further compromised, potentially dropping in dim light that the images are only reached 40-60% for clear images and 20% in blurry images.